Konsep Properti, Kepemilikan, dan Kontrak: Studi Komprehensif dalam Hukum Ekonomi Syariah - Debby Triana Dewi Debby; Hafiza Astri Hafiza (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2025)
The development of Islamic economics requires a comprehensive conceptual understanding of the legal foundations of muʿāmalāt to ensure that economic practices do not become confined to mere contractual formalism. This article aims to provide a comprehensive analysis of the concepts of wealth (al-māl), ownership (al-milkiyyah), and contracts, as well as their integrative relationship within the framework of Islamic economic law. The study employs a qualitative method with a normative–conceptual approach, drawing on a literature review of primary sources of Islamic law and relevant contemporary academic scholarship. The findings indicate that wealth in Islam is understood as a trust (amānah) encompassing economic, social, and moral dimensions; ownership functions as legal legitimacy for the utilization of wealth within Sharīʿa constraints and social responsibility; while contracts serve as legal instruments that lawfully and equitably connect wealth and ownership in a benefit-oriented manner. The study’s main contribution affirms that these three concepts are systemic and inseparable. Reducing contracts to mere formal agreements risks obscuring the objectives of maqāṣid al-sharīʿa. Therefore, the conceptual integration of wealth, ownership, and contracts constitutes an essential prerequisite for the development of Islamic economic practices that are not only legally compliant but also reflective of justice, ethical values, and social welfare in the contemporary economic context.